Urban Air Pollution in India - Narain, Urvashi (2012)
This article describes the main efforts undertaken to stem the growth of air pollution in Indian cities. We begin by examining trends in air quality across the country. This is followed by a description of the legal and institutional framework and policies for controlling air pollution in India. Next we report on efforts to improve air quality in Delhi. We conclude by describing recent actions to control air pollution in cities other than Delhi.